The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0300060520929615
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a inhibits the inflammatory response of microglia by targeting HMGA2 in intracerebral hemorrhage

Abstract: Objective Intracerebral hemorrhage (ICH) is a common cerebrovascular disease with high mortality and poor prognosis. Therefore, the biological function and underlying molecular mechanism of miR-26a in inflammatory injury following ICH was investigated. Methods The potential role of miR-26a was investigated in lipopolysaccharide (LPS)-treated microglial cells by quantitative real-time PCR. To explore the potential role of HMGA2 in the miR-26a-regulated inflammatory response, LPS-induced microglial cells were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…In our study, we showed that the expression levels of miR-26a were downregulated following LPS stimulation, indicating that miR-26a may be involved in macrophage regulation. Furthermore, overexpression of miR-26a was associated with a significant decrease in the production of TNF-α, IL-6, and IL-1β, while knockdown of miR-26a exhibited a reverse effect in regulating the production of these proteins, consistent with previous research [ 20 , 39 ]. However, it is regrettable that there is a relatively modest effect in survival outcomes from mice with LPS-induced excessive inflammation after miR-26a administration.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we showed that the expression levels of miR-26a were downregulated following LPS stimulation, indicating that miR-26a may be involved in macrophage regulation. Furthermore, overexpression of miR-26a was associated with a significant decrease in the production of TNF-α, IL-6, and IL-1β, while knockdown of miR-26a exhibited a reverse effect in regulating the production of these proteins, consistent with previous research [ 20 , 39 ]. However, it is regrettable that there is a relatively modest effect in survival outcomes from mice with LPS-induced excessive inflammation after miR-26a administration.…”
Section: Discussionsupporting
confidence: 90%
“…Importantly, this downregulation was associated with increased IL-6 expression [ 19 ]. Subsequently, miR-26a was found to markedly reduce IL-6, IL-1β, and TNF-α expression by targeting high-mobility group AT-hook 2 in lipopolysaccharide (LPS)-treated microglial cells [ 20 ]. Furthermore, miR-26a overexpression in mouse microglial cells significantly suppressed pro-inflammatory cytokine expression in mouse brains and markedly improved the neurological behavior and rotarod test performance of mice after intracerebral hemorrhage.…”
Section: Introductionmentioning
confidence: 99%
“… 18 In addition, Jin et al found that miR-26a inhibits the inflammatory responses of microglia by targeting HMGA2 in intracerebral hemorrhage. 17 Consistently, these results indicate that Hmga2 promotes LPS-induced inflammation through the NF-κB pathway in BV2 cells.…”
Section: Discussionsupporting
confidence: 72%
“…15 Moreover, HMGA2 is a driver of inflammation in conditions such as acute liver injury, intracerebral hemorrhage and cardiac dysfunction. [16][17][18] However, its role in retinal inflammation and whether Nr1d1 can regulate it should be investigated further.…”
Section: Introductionmentioning
confidence: 99%
“…There should be a 15-min rest interval between each test ( 46 ). Before surgery, the baseline of rats is around 150 s ( 86 ), while the mice are around 250~300 s ( 45 , 87 ). Animals with hemorrhagic damage tend to fall faster than normal ones ( 88 ).…”
Section: Common Behavioral Assessmentsmentioning
confidence: 99%